Student Engagement in Physics Test: Administrating Time on Test-Item for Mechanical Physics - Rizki Zakwandi; Alfiansah Sandion Prakoso; Duden Saepuzaman; Lina Aviyanti; Siti Nurhadianti Muhajir (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2026)
Student engagement in physics assessment can be evaluated through both final outcomes and the fundamental problem-solving process. This study seeks to examine the correlation among item complexity, completion time, and student performance on a physics mechanic’s test. The research utilized a quantitative methodology through a cross-sectional survey design with 50 participants from the physics education program. Data were collected through a web-based, computer-administered assessment comprising 20 two-tiered items covering kinematics, dynamics, momentum and impulse, as well as work and energy topics. The complexity of the item was assessed according to the number of competencies engaged, encompassing conceptual, mathematical, graphical, data-related, and inter-variable relationships. The findings demonstrate that higher item complexity is associated with longer completion times, which may reflect greater cognitive effort or increased cognitive load. This increase in time did not correlate with enhanced performance; instead, it indicated a pattern toward decreasing scores, exhibiting a negative correlation of -0.32 between complexity and scores. Moreover, the correlation between completion time and performance fluctuates based on the subject matter and type of competency. Mathematical competencies demonstrate the most effective pattern, characterized by high scores and relatively brief completion times, while graphical competencies are associated with longer completion times and lower scores. The findings indicate that response time signifies both engagement and the difficulty level encountered by students. Consequently, integrating response time with performance data provides a more comprehensive understanding of student engagement. This research underscores the necessity of enhancing representational competencies and employing process-based data to create more effective physics assessments.